Attitudes of psychiatrists towards people with mental illness: a cross-sectional, multicentre study of stigma in 32 European countriesResearch in context - Dorottya Őri; Péter Szocsics; Tamás Molnár; Lucie Bankovska Motlova; Olga Kazakova; Sabrina Mörkl; Michael Wallies; Mohamed Abdulhakim; Sylvie Boivin; Krista Bruna; Carolina Cabaços; Elvira Anna Carbone; et al. (EClinicalMedicine, 2023)
Summary: Background: Mental health-related stigma occurs among the public and professionals alike. The lived experience of mental illness has been linked to less stigmatising attitudes. However, data on psychiatrists and the relationship between stigmatising attitudes and psychotherapeutic activity or case discussion groups remains scarce. Methods: A cross-sectional multicentre study was performed in 32 European countries to investigate the lived experiences and attitudes of psychiatrists toward patients with mental illness as well as the relationship between stigma, psychosocial and professional factors. The self-reported, anonymous, internet-based Opening Minds Stigma Scale for Health Care Providers was used to measure the stigmatising attitudes. The survey was translated into the local language of each participating country. All participants were practising specialists and trainees in general adult or child and adolescent psychiatry. The study took place between 2nd October, 2019 and 9th July, 2021 and was preregistered at ClinicalTrial.gov (NCT04644978). Findings: A total of 4245 psychiatrists completed the survey. The majority, 2797 (66%), had completed training in psychiatry, and 3320 (78%) worked in adult psychiatry. The final regression model showed that across European countries more favourable attitudes toward people with mental illness were statistically significantly associated with the lived experience of participants (including seeking help for their own mental health conditions (d = −0.92, 95% confidence interval (CI) = −1.68 to −0.15, p = 0.019), receiving medical treatment for a mental illness (d = −0.88, 95% CI = −1.71 to −0.04, p = 0.040), as well as having a friend or a family member similarly affected (d = −0.68, 95% CI = −1.14 to −0.22, p = 0.004)), being surrounded by colleagues who are less stigmatising (d = −0.98, 95% CI = −1.26 to −0.70, p < 0.001), providing psychotherapy to patients (d = −1.14, 95% CI = −1.63 to −0.65 p < 0.001), and being open to (d = −1.69, 95% CI = −2.53 to −0.85, p < 0.001) and actively participating in (d = −0.94, 95% CI = −1.45 to −0.42, p < 0.001) case discussion, supervision, or Balint groups. Interpretation: Our study highlights the importance of psychotherapy training, supervision, case discussions and Balint groups in reducing the stigmatising attitudes of psychiatrists toward patients. As the findings represent cross-national predictors, Europe-wide policy interventions, national psychiatric education systems and the management of psychiatric institutions should take these findings into consideration. Funding: National Youth Talent Award (Ministry of Human Resources, Hungary, (NTP-NFTÖ-20-B-0134). All authors received no funding for their contribution.